Clinical characterization and identification of duplication breakpoints in a Japanese family with Xq28 duplication syndrome including MECP2. Issue 4 (29th January 2014) - Fukushi, Daisuke; Yamada, Kenichiro; Nomura, Noriko; Naiki, Misako; Kimura, Reiko; Yamada, Yasukazu; Kumagai, Toshiyuki; Yamaguchi, Kumiko; Miyake, Yoshishige; Wakamatsu, Nobuaki
<x xml:space="preserve">Abstract</x> Xq28 duplication syndrome including MECP2 is a neurodevelopmental disorder characterized by axial hypotonia at infancy, severe intellectual disability, developmental delay, mild characteristic facial appearance, epilepsy, regression, and recurrent infections in males. We identified a Japanese family of Xq28 duplications, in which the patients presented with cerebellar ataxia, severe constipation, and small feet, in addition to the common clinical features. The 488‐kb duplication spanned from L1CAM to EMD and contained 17 genes, two pseudo genes, and three microRNA‐coding genes. FISH and nucleotide sequence analyses demonstrated that the duplication was tandem and in a forward orientation, and the duplication breakpoints were located in AluSc at the EMD side, with a 32‐bp deletion, and LTR50 at the L1CAM side, with "tc" and "gc" microhomologies at the duplication breakpoints, respectively. The duplicated segment was completely segregated from the grandmother to the patients. These results suggest that the duplication was generated by fork‐stalling and template‐switching at the AluSc and LTR50 sites. This is the first report to determine the size and nucleotide sequences of the duplicated segments at Xq28 of three generations of a family and provides the genotype–phenotype correlation of the patients harboring the specific duplicated segment. © 2014 Wiley Periodicals, Inc.